The Influence of Cash and Non-Cash Transactions on Al-Jihad Mosque Al-Jihad Medan Baru Al-Jihad Mosque Congregation Decisions - Siti Khairani; Tri Inda Fadhila Rahma; Faisal Umardani Hasibuan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The development of financial technology has encouraged mosques to adopt non-cash transaction systems in managing infaq. This study aims to examine the effect of cash and non-cash transaction usage on infaq decisionmaking among worshippers at Al-Jihad Mosque, Medan Baru. This research employed a quantitative method with a comparative approach. Data were collected through a survey using questionnaires distributed to 120 respondents who were worshippers of Al-Jihad Mosque. The sampling technique used was purposive sampling. Data analysis was preceded by validity and reliability tests, followed by a normality test to determine the appropriate hypothesis testing method. The results of the normality test indicated that the data were not normally distributed; therefore, the hypothesis was tested using the Wilcoxon test. The results showed that the Asymp. Sig. (2-tailed) value was 0.000, which is less than the significance level of 0.05. This finding indicates a significant difference in infaq decisions between worshippers who use cash transactions and those who use non-cash transactions. The results suggest that transaction methods have a significant influence on worshippers’ infaq decisions. Therefore, the implementation and development of non-cash transaction systems in mosques are expected to facilitate infaq practices and encourage greater participation among worshippers